2021
DOI: 10.1109/tvcg.2020.3030469
|View full text |Cite
|
Sign up to set email alerts
|

Topology Density Map for Urban Data Visualization and Analysis

Abstract: Fig. 1. Analyzing the influence of road topology and traffic conditions on POI accessibility: density distribution before (a) and after (b) removing the selected road segments FE and ED; and density distribution before (c) and after (d) slowing down the average speeds of the selected road segments MN and NO.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…When utilizing the density map in an urban area, the road network's topology is an essential factor to be considered. Therefore, Feng et al (2021) proposed a novel method named topology density map (Figure 3c) to visualize the urban data. They took the topology of the road network, the direction of the road into account which makes the density estimation more accurate in visualizing urban data.…”
Section: Improving Current Visualization Techniques To Visualize Mass...mentioning
confidence: 99%
See 1 more Smart Citation
“…When utilizing the density map in an urban area, the road network's topology is an essential factor to be considered. Therefore, Feng et al (2021) proposed a novel method named topology density map (Figure 3c) to visualize the urban data. They took the topology of the road network, the direction of the road into account which makes the density estimation more accurate in visualizing urban data.…”
Section: Improving Current Visualization Techniques To Visualize Mass...mentioning
confidence: 99%
“…The results for the model can be encoded into different visual techniques with different visual representations. For instance, Feng et al (2021) proposed a novel approach to draw a density map to visualize the traffic data, considering the road topology and temporal variants. This novel density map can reveal the impact of the POIs (point of interests) in the urban area.…”
mentioning
confidence: 99%
“…Visualization has been widely used for exploratory data analysis and decision making in various domains including stock trading [39], online education [23] and urban planning [15]. However, most existing tools for creating visualizations heavily rely on users' manual specifications [19].…”
Section: Visualization Recommendationmentioning
confidence: 99%
“…In particular, they showed that thefts tend to concentrate more than robberies and robberies more than burglaries. Poveda (2012) studied socio-economic and violent crime in seven cities, showing that cities' economic deprivation (SPICER et al, 2016) VitalVizor Ye, 2018), (FENG et al, 2020) Trajgraph (Huang et al, 2016) VitalVizor Ye, 2018) and high population density are strong factors in homicide rates. Additionally, they found that economic growth, inequality, poverty, and human capital had a negative influence on violent crimes.…”
Section: Socio-economic Based Crime Analysismentioning
confidence: 99%
“…Discussed and suggested by domain experts, we decided to take the streets intersection as the 'analysis unit' for practical and substantial reasons: (i) due the availability of input data, urban features are unknown for us (FENG et al, 2020); (ii) When a crime event occurs generally, the police officer reports the location as the intersection of streets (BRAGA; HUREAU; PA-PACHRISTOS, 2011); (iii) we can only measure the average of the criminality in a road segment, whilst the crime events positions are not exact (BRAGA; HUREAU; PAPACHRISTOS, 2011); (iv) Qualitative research suggests that robbers find street corners to be good locations to locate potential victims (JACOBS, 2000;JEAN, 2007); and (v) inner-city residents meet, socialize, and sometimes live out significant portions of their daily lives on streets corners (LIEBOW, 2003).…”
Section: Data Modellingmentioning
confidence: 99%